Differences in Burden Severity in Adult-Child Family Caregivers and Spousal Caregivers of Persons with Dementia. Issue 5 (4th July 2021) - Kunicki, Zachary J.; Gaudiano, Brandon A.; Miller, Ivan W.; Tremont, Geoffrey; Salloway, Stephen; Darling, Ellen; Broughton, Monica K.; Kraines, Morganne A.; Hoopes, Ryan; Epstein-Lubow, Gary
ABSTRACT: Researchers are continuing to focus on the nature and sources of burden of family caregivers of persons living with dementia. Caregiving stress and burden are assessed and addressed by social workers, including at high-risk times such as hospitalization. This study tested whether adult-child family caregivers experience greater perceived burden than spousal caregivers, accounting for risks of acute stress which can accompany hospitalization for their care recipient, where social workers may be meeting with family caregivers for the first time. Family caregivers (N = 76; n = 42 adult-child; n = 34 spouse) were recruited during care-recipient clinical treatment. The settings of care included an outpatient memory care program and an inpatient geriatric psychiatry service. Results showed that adult-child caregivers reported greater burden as compared with spousal caregivers, but no differences regarding depressive symptoms, perceived stress, or grief. After controlling for demographics and location of care, being an adult-child caregiver remained a predictor of greater burden severity. Being an adult-child family caregiver may place an individual at increased risk for experiencing high burden. These findings suggest socials workers should consider how adult-child caregivers may benefit from strategies to address and reduce burden, beyond those typically offered to spousal caregivers.